Early-strength decorative ultra-high performance concrete and preparation method thereof

By adding nano silica sol and modifier to decorative ultra-high performance concrete, the early reaction of gelled materials is promoted, the problem of low production efficiency in low temperature environments is solved, and the early strength is significantly improved and the production efficiency is improved. .

CN119462000APending Publication Date: 2025-02-18江苏博思通新材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411436500.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In low temperature environments, the curing cycle of decorative ultra-high performance concrete is extended, resulting in reduced production efficiency.

Method used

Using early-strength decorative ultra-high performance concrete formula, nanosilica sol and modifier are added, and the nanosilica surface is modified through modifiers, so that it can participate in the reaction in the early stage of cement hydration, and promote gelling materials , thereby increasing the intensity at 24h early.

Benefits of technology

It significantly improves the early strength of decorative UHPC 24h, meets the mold release needs of decorative UHPC products, improves production efficiency, and does not affect the development of later strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses early strength type decorative ultra-high performance concrete and a preparation method thereof. The early strength type decorative ultra-high performance concrete is prepared from the following raw materials in parts by weight: 35 to 45 parts of cement, 40 to 50 parts of sand, 2 to 5 parts of metakaolin, 5 to 10 parts of silica fume, 5 to 10 parts of calcium carbonate, 1 to 3 parts of nano-silica sol, 0.5 to 1.5 parts of water reducing agent, 0.05 to 0.3 part of modifier, 1 to 6 parts of fiber and 8 to 12 parts of water. And the modifier is one or a combination of more of a polyepoxy organic compound, a polyhydric alcohol organic compound, a polyene organic compound or a polyether organic compound containing hydroxyl, ester bonds or ether bonds. The nano silicon dioxide sol can promote the reaction of a cementing material in the UHPC, and meanwhile, the modifier can maintain the fresh mixing performance of the UHPC, so that the early strength of the decorative UHPC is finally improved, the development of the later strength is not influenced, the demolding requirement of a decorative UHPC product can be met, and the production efficiency of the decorative UHPC product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to an early-strength decorative ultra-high performance concrete and a preparation method thereof. Background Art

[0002] As people's requirements for architectural decoration and environmental beautification increase, many architects innovatively use concrete as an integrated structural decoration material to give full play to its aesthetic and spatial expression. Ultra-high performance concrete (UHPC), as an emerging concrete material, has the characteristics of ultra-high durability, high fluidity, and ultra-high mechanical properties, and is rapidly being used in the field of architectural decoration.

[0003] Decorative UHPC concrete is generally available in two modes: prefabricated and cast-in-place. According to specific project statistics, factory prefabrication is still the main method. The demoulding time of decorative UHPC products determines its production efficiency, especially in the low temperature environment in winter, when the UHPC curing cycle is extended, resulting in reduced production efficiency. Summary of the invention

[0004] Purpose of the invention: In order to solve the problems existing in the prior art, the purpose of the present invention is to provide an early-strength decorative ultra-high performance concrete and a preparation method thereof.

[0005] Technical solution: In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0006] An early-strength decorative ultra-high performance concrete comprises the following raw materials in parts by weight:

[0007] 35-45 parts of cement, 40-50 parts of sand, 2-5 parts of metakaolin, 5-10 parts of silica fume, 5-10 parts of calcium carbonate,

[0008] Nano silica sol 1-3 parts, water reducer 0.5-1.5 parts, modifier 0.05-0.3 parts, fiber 1-6 parts,

[0009] 8-12 parts water;

[0010] The modifier is one or a combination of polyepoxy, polyol, polyolefin or polyether organic compounds containing hydroxyl, ester bond or ether bond.

[0011] As a specific implementation scheme, the cement is 52.5 type white silicate cement.

[0012] As a specific implementation scheme, the sand is quartz sand obtained by mixing 100-120 mesh quartz sand and 60-80 mesh quartz sand in a mass ratio of (2-4):(8-6); the metakaolin is 1200-1400 mesh; and the calcium carbonate is 1000-1500 mesh white calcium carbonate.

[0013] As a specific implementation scheme, the silica fume is white silica fume with a silicon dioxide content greater than 90%.

[0014] As a specific implementation scheme, the nano-silica sol has a size of 15-30 nm and a solid content of 25-35%.

[0015] As a specific implementation scheme, the water reducer is a polycarboxylic acid water reducer with a solid content of 25-35% and a water reduction rate of more than 35%.

[0016] As a specific implementation, the modifier is one or more of polyethylene oxide, glycerol, polyisobutylene, and polyether-modified silicon.

[0017] As a specific implementation scheme, the fiber is one or more of polyoxymethylene fiber, polypropylene fiber, and steel fiber, with a fiber diameter of 0.1-0.3 mm and a length of 6-16 mm.

[0018] The present invention also provides a method for preparing the early-strength decorative ultra-high performance concrete, comprising the following steps:

[0019] (1) Premix cement, sand, silica fume, metakaolin and calcium carbonate according to a certain proportion and stir evenly to form component A;

[0020] (2) Add the modifier to the nano-silica sol in proportion and stir evenly, add the water reducer and stir evenly, add water and stir evenly to form component B;

[0021] (3) Add component B to component A and stir, add fiber and stir, make slurry, inject into the prepared mold, cure and demould, so as to obtain the early-strength decorative ultra-high performance concrete.

[0022] As a specific implementation scheme, in step (1), cement, sand, silica fume, metakaolin, and calcium carbonate are premixed and stirred in proportion for 10-15 minutes;

[0023] In step (3), component B is added to component A and stirred for 7-10 minutes, and the fiber is added and stirred for 3-5 minutes.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0025] 1. The added nano-silica, as the core site of cement hydration, participates in the reaction in the early stage of cement hydration, promotes the reaction of the cementitious material in UHPC, improves the 24h early strength of decorative UHPC without affecting the development of later strength, can meet the demoulding requirements of decorative UHPC products, and improve its production efficiency.

[0026] 2. The introduction of nano-silica reduces the fluidity of freshly mixed UHPC. First, the surface of nano-silica is modified by a modifier so that the surface of nano-silica is coated with a layer of modifier. Due to the presence of organic groups in the modifier, the surface tension between particles is reduced. Due to the certain chain length, a certain steric hindrance is provided, so that effective slip occurs between particles, and the freshly mixed performance of UHPC is maintained. After the mixing period, the alkalinity of cement increases, and the hydroxyl groups in the slurry environment attack the ester bonds or ether bonds in the modifier. Nano-silica is gradually released and becomes the core site of cement hydration, thereby promoting the early strength development of UHPC without affecting the later strength of UHPC. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The raw materials used in the following examples and comparative examples are as follows:

[0029] The cement is 52.5 type white silicate cement.

[0030] The sand is quartz sand mixed with 100-120 mesh quartz sand and 60-80 mesh quartz sand in a ratio of 3:7.

[0031] The mesh size of metakaolin is 1200-1400 mesh.

[0032] Silica fume is white silica fume with a silicon dioxide content greater than 90%.

[0033] Calcium carbonate is 1000-1500 mesh white calcium carbonate.

[0034] Example 1

[0035] formula:

[0036] 40 parts of cement, 45 parts of sand, 5.5 parts of silica fume, 2.5 parts of metakaolin, 6.5 parts of calcium carbonate, 2 parts of nano-silica sol, 1 part of water reducer, 0.1 part of modifier, 1.5 parts of polyoxymethylene fiber, and 9 parts of water.

[0037] Among them, the nano-silica sol is 15-30nm and has a solid content of 30%; the water reducer is a polycarboxylic acid water reducer with a solid content of 30% and a water reduction rate of 40%; the modifier is polyethylene oxide and propylene glycol added in a ratio of 10:1; the diameter of the polyoxymethylene fiber is 0.2mm and the length is 12mm.

[0038] Preparation method:

[0039] Cement, sand, silica fume, metakaolin and calcium carbonate are added into a mixing container and stirred for 10 minutes to obtain a dry powder premix; nano silica sol, water reducer, modifier and water are evenly mixed and added into the dry powder premix and stirred for 7 minutes; polyoxymethylene fiber is added and stirred for 3 minutes, and then injected into a mold, cured and demolded to obtain an early-strength decorative UHPC concrete product.

[0040] Example 2

[0041] formula:

[0042] 43 parts of cement, 40 parts of sand, 6.5 parts of silica fume, 3.5 parts of metakaolin, 6.5 parts of calcium carbonate, 4 parts of nano-silica sol, 0.8 parts of water reducer, 0.2 parts of modifier, 1.5 parts of polyoxymethylene fiber, and 10 parts of water.

[0043] Among them, the nano-silica sol is 15-30nm and has a solid content of 25%; the water reducer is a polycarboxylic acid water reducer with a solid content of 35% and a water reduction rate of 40%; the modifier is polyether modified silicon and propylene glycol added in a mass ratio of 5:1; the diameter of the polyoxymethylene fiber is 0.2mm and the length is 6mm.

[0044] Preparation method:

[0045] Cement, sand, silica fume, metakaolin and calcium carbonate are added into a mixing container and stirred for 10 minutes to obtain a dry powder premix; nano silica sol, water reducer, modifier and water are evenly mixed and added into the dry powder premix and stirred for 7 minutes; polyoxymethylene fiber is added and stirred for 3 minutes, and then injected into a mold, cured and demolded to obtain an early-strength decorative UHPC concrete product.

[0046] Example 3

[0047] formula:

[0048] 38 parts of cement, 45 parts of sand, 6.5 parts of silica fume, 3.5 parts of metakaolin, 6.5 parts of calcium carbonate, 3 parts of nano-silica sol, 0.8 parts of water reducer, 0.3 parts of modifier, 1.5 parts of polyoxymethylene fiber, and 10 parts of water.

[0049] Among them, the nano-silica sol is 15-30nm and has a solid content of 35%; the water reducer is a polycarboxylic acid water reducer with a solid content of 30% and a water reduction rate of 40%; the modifier is polyisobutylene and polyether modified silicon added in a mass ratio of 1:1; the diameter of the polyoxymethylene fiber is 0.2mm and the length is 16mm.

[0050] Preparation method:

[0051] Cement, sand, silica fume, metakaolin and calcium carbonate are added into a mixing container and stirred for 10 minutes to obtain a dry powder premix; nano silica sol, water reducer, modifier and water are evenly mixed and added into the dry powder premix and stirred for 7 minutes; polyoxymethylene fiber is added and stirred for 3 minutes, and then injected into a mold, cured and demolded to obtain an early-strength decorative UHPC concrete product.

[0052] Comparative Example 1

[0053] formula:

[0054] 40 parts of cement, 45 parts of sand, 5.5 parts of silica fume, 2.5 parts of metakaolin, 6.5 parts of calcium carbonate, 1 part of water reducer, 1.5 parts of polyoxymethylene fiber, and 9 parts of water.

[0055] Among them, the water reducer is a polycarboxylic acid water reducer with a solid content of 30% and a water reduction rate of 40%; the diameter of the polyoxymethylene fiber is 0.2mm and the length is 12mm.

[0056] Preparation method:

[0057] Cement, sand, silica fume, metakaolin and calcium carbonate are added into a mixing container and stirred for 10 minutes to obtain a dry powder premix; a water reducer and water are evenly mixed and added into the dry powder premix and stirred for 7 minutes; polyoxymethylene fiber is added and stirred for 3 minutes; the mixture is injected into a mold, cured and demolded to obtain an early-strength decorative UHPC concrete product.

[0058] Comparative Example 2

[0059] formula:

[0060] 40 parts of cement, 45 parts of sand, 5.5 parts of silica fume, 2.5 parts of metakaolin, 6.5 parts of calcium carbonate, 2 parts of nano-silica sol, 1 part of water reducing agent, 1.5 parts of polyoxymethylene fiber, and 9 parts of water.

[0061] Among them, the nano-silica sol is 15-30nm and has a solid content of 30%; the water reducer is a polycarboxylic acid water reducer with a solid content of 30% and a water reduction rate of 40%; the diameter of the polyoxymethylene fiber is 0.2mm and the length is 12mm.

[0062] Preparation method:

[0063] Cement, sand, silica fume, metakaolin and calcium carbonate are added into a mixing container and stirred for 10 minutes to obtain a dry powder premix; nano silica sol, water reducer and water are evenly mixed and added into the dry powder premix and stirred for 7 minutes; polyoxymethylene fiber is added and stirred for 3 minutes, and then injected into a mold, cured and demolded to obtain an early-strength decorative UHPC concrete product.

[0064] 1. Performance Testing

[0065] The ultra-high performance concrete materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to GB / T17671. The test results are shown in the following table:

[0066]

[0067] Comparative Example 1: No nano silica sol and modifier were added to Example 1

[0068] Comparative Example 2 is relative to Example 1 except that nano-silica sol is added without adding a modifier.

[0069] From the results in the above table, it can be seen that the addition of nano-silica reduces the expansion from 315mm to 145. After adding the modifier, the expansion reaches 315. The modified nano-silica greatly reduces the impact on the fresh performance of UHPC slurry. By comparing the embodiment with the comparative example, it is found that the increase in early strength before 16h is very obvious, and the increase in early strength gradually decreases after 24h. The 28d test results show that the strengths of each group tend to be close, and nano-silica has a significant enhancement effect on the early strength of UHPC and will not reduce the later strength.

[0070] The implementation modes of the present invention have been described in detail above in conjunction with specific embodiments, but the present invention is not limited to the above-mentioned implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. An early-strength decorative ultra-high performance concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of cement, 40-50 parts of sand, 2-5 parts of metakaolin, 5-10 parts of silica fume, 5-10 parts of calcium carbonate, Nano silica sol 1-3 parts, water reducer 0.5-1.5 parts, modifier 0.05-0.3 parts, fiber 1-6 parts, 8-12 parts water; The modifier is one or a combination of polyepoxy, polyol, polyolefin or polyether organic compounds containing hydroxyl, ester bond or ether bond.

2. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The cement is 52.5 type white silicate cement.

3. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The sand is quartz sand obtained by mixing 100-120 mesh quartz sand and 60-80 mesh quartz sand in a mass ratio of (2-4):(8-6); the metakaolin is 1200-1400 mesh; and the calcium carbonate is 1000-1500 mesh white calcium carbonate.

4. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The silica fume is white silica fume, and the silicon dioxide content is greater than 90%.

5. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The nano-silicon dioxide sol has a size of 15-30 nm and a solid content of 25-35%.

6. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent with a solid content of 25-35% and a water reducing rate of more than 35%.

7. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The modifier is one or more of polyethylene oxide, glycerol, polyisobutylene and polyether modified silicon.

8. The early-strength decorative ultra-high performance concrete according to claim 1, characterized in that: The fiber is one or more of polyoxymethylene fiber, polypropylene fiber and steel fiber, and the fiber diameter is 0.1-0.3 mm and the length is 6-16 mm.

9. The method for preparing the early-strength decorative ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Premix cement, sand, silica fume, metakaolin and calcium carbonate according to a certain proportion and stir evenly to form component A; (2) Add the modifier to the nano-silica sol in proportion and stir evenly, add the water reducer and stir evenly, add water and stir evenly to form component B; (3) Add component B to component A and stir, add fiber and stir, make slurry, inject into the prepared mold, cure and demould, so as to obtain the early-strength decorative ultra-high performance concrete.

10. The method for preparing the early-strength decorative ultra-high performance concrete according to claim 9, characterized in that: In step (1), cement, sand, silica fume, kaolin and calcium carbonate are premixed and stirred in proportion for 10-15 minutes; In step (3), component B is added to component A and stirred for 7-10 minutes, and the fiber is added and stirred for 3-5 minutes.

Citation Information

Patent Citations

  • High-fluidity ultra-high performance concrete material

    CN113620661A

  • Liquid colloid nano silicon oxide as well as preparation method and application thereof

    CN114477191A

  • Additive for preparing high-performance concrete admixture from spontaneous combustion coal gangue and application of additive

    CN115403301A

  • Borehole cement slurry additive, method for storing same, borehole cement slurry, and borehole cementing method

    US20220195282A1

  • Colloidal silica particles, process for producing the same, and silica sol in organic solvent, silica sol in polymerizable compound, and silica sol in dicarboxylic anhydride each obtained from the same

    WO2009101974A1